The Impact Of Taxation In Circular Economy/New Tax Thinking :The Case Study USA - Aziz, Hemin Tawfiq; mohammed, Hunar jabar; Hamawandy, Nawzad Majeed; Abubakr, Zaito Awla; Jamil, Diyar Abdulmajeed; Othman, Bestoon (The journal of contemporary issues in business and government, 2021)
The evolution of linear economies has been, inter alia, driven by a market that does not tell the „ecological truth‟ as most “environmental externalities” (such as environmental damage caused by extraction but also by the transport or use of resources are not reflected in market prices. In a circular economy, optimization of the use of non-renewable resources implies taking into account and integrating quantitatively these "externalities" in the calculation of the overall value of a product or a service, using statistics gathered from publicly available sources, such as the U.S. Census Bureau. The regression analysis includes economic data from all 50 U.S states from 10 years of a 12-year period. The resulting findings indicate that a tenuous connection does exist between taxes and circular economy, but that the relationship is not consistent or consistently significant across many different possible kinds of circular economy. Thus, eschewing any notions of a one size fits all tax policy. Furthermore, a determination is made that other, non-tax, vi economic and social factors are actually more important to our understanding of circular economy and of what constitutes good policy in this field of economic data